Chemical and Electrochemical Stability of Nitrogen and Sulphur Doped Mesoporous Carbons. (10th April 2016) - Perazzolo, Valentina; Grądzka, Emilia; Durante, Christian; Pilot, Roberto; Vicentini, Nicola; Rizzi, Gian Andrea; Granozzi, Gaetano; Gennaro, Armando
Graphical abstract: Highlights: Morphological and chemical modifications were observed on MCs in acidic electrolyte; In alkaline electrolyte a substantial chemical stability was preserved in doped MCs; Nitrogen doped MCs have superior thermal stability with respect to sulfur doped ones; Pyridinic and pyrrolic groups are oxidized during the accelerated degradation tests; N-graphitic and thiophenic groups show intrinsic thermodynamic stability. Abstract: Mesoporous carbons (MCs) are porous materials with high surface area and superior mass transport efficiency than traditional carbon materials that make them attractive to electrocatalytic applications. Doped carbons are particularly interesting due to their possible use as metal-free catalysts for oxygen reduction reaction (ORR) or as electrode support for Pt based catalysts. One of the key points to address for the doped MCs implementation in electrochemical devices, subjected to strong electrochemical stresses, is to determine their durability. In this paper we investigate the chemical modification in nitrogen and sulfur doped or co-doped MCs after ex situ accelerated degradation test (ADT) consisting in ten thousand voltammetric cycles in a potential window of −0.25/+ 1.0 V vs. SCE, in Ar saturated 0.5 M H2 SO4, 0.1 M HClO4 or 0.1 M KOH electrolytes. The morphological, chemical and electrochemical properties of doped MCs before and after ADT were evaluated by scanning electron microscopy, thermal gravimetric analysis, Raman and X-ray photoemission spectroscopies, cyclic and linear sweep voltammetries. The carbon materials have proved to keep the porous structure after the ADT, without evident structural collapse. It was found that in acidic and in a lower degree in alkaline electrolytes, pyridinic and pyrrolic functional groups can be oxidized to nitrogen oxide groups, whereas N-graphitic and thiophenic like groups are less affected by the electrochemical oxidation. After ADT, nitrogen doped MCs and, to a lesser extent, sulfur doped MCs resulted to partially lose their catalytic activity towards ORR.